Internalisasi Nilai Karakter Disiplin Untuk Menumbuhkan Budaya Positif di Lingkungan Sekolah - Akmal Rijal; Idrus Affandi; Aceng Kosasih; Momod Abdul Somad (Universitas Negeri Padang, 2023)
This study aims to describe the effectiveness of internalizing disciplinary character values to foster a positive culture in the school environment. The type of this research was a Mixed-methods experimental design with the subjects SD Negeri 11 and 36 Lubuklinggau students to collect data by applying internalization of disciplinary character values in school. The instruments are interview forms, questionnaires of students' knowledge and attitudes, and questionnaires internalizing disciplinary character values. Data reduction, data presentation, data analysis, interpretation, conclusion drawing and verification are all steps in the analysis of qualitative data. Quantitative data from the experimental class to the control class were evaluated as descriptive statistics. The findings show that empirical models in the development of student disciplinary character require consistency because, in schools, teachers are not used to collaborating with students to correct existing mistakes but can only provide punishment. Respondents (75.00%) rated the interaction, internalization of discipline, class agreement criteria, teacher control, more than half of respondents (56.25%), and positive discipline (86.11%). The RAI Index score was 6.60. This study offers important insights into the roles of classroom agreement, teacher control, and positive discipline in predicting different types of value regulation, including external, introjection, identified, and integrated regulation. This is an intriguing finding.